Exploring Changes in Valued Action in the Presence of Chronic Debilitating Pain in Acceptance and Commitment Therapy for Youth – A Single-Subject Design Study - Kemani, Mike K.; Olsson, Gunnar L.; Holmström, Linda; Wicksell, Rikard K. (Frontiers in Psychology, 2016)
Objective: The objective of the study was to improve the understanding of processes of change in Acceptance and Commitment Therapy for youths with chronic debilitating pain by exploring the relation between individual change patterns in pain intensity and valued activities. Method: A single-subject design across three adolescents suffering from longstanding debilitating pain was utilized. Pain intensity and participation in valued activities were rated daily. Visual analysis of the graphed data was performed to evaluate the effects of the intervention, and the relationship between pain intensity and values-based activity. Results: The graphed data illustrated that pain levels did not decrease from the baseline period to the follow-up period. In contrast, compared to baseline ratings values oriented behaviors increased from the start of treatment to the follow-up period. Conclusion: Results illustrate that increases in valued activities may occur also without corresponding decreases in pain, and warrant further research on change processes in ACT for youths suffering from chronic pain.